Relationship marketing in Latin American context : Implications for small Finnish software companies in Latin American B2B partnerships - Korkalainen, Anna (fi=Turun yliopisto|en=University of Turku|, 2017)
After a productivity decrease of established national export industries in Finland such as mobile and paper industries, innovative, smaller companies with the intentions to internationalize right from the start have been proliferating. For software companies early internationalization is an especially good opportunity, as Internet usage becomes increasingly homogeneous across borders and software products often do not need a physical distribution channel. Globalization also makes Finnish companies turn to unfamiliar export markets like Latin America, a very untraditional market for Finns. Relationships consisting of Finnish and Latin American business partners have therefore not been widely studied, especially from a new-age software company’s perspective. To study these partnerships, relationship marketing theory was taken into the core of the study, as its practice focuses mainly on establishing and maintaining relationships with stakeholders at a profit, so that the objectives of all parties are met, which is done by a mutual exchange and fulfillment of promises. The most important dimensions of relationship marketing were identified as trust, commitment and attraction, which were then focused on, as the study aims to understand the implications Latin American business culture has for the understanding, and hence, effective application of relationship marketing in the Latin American market. The question to be answered consecutively was how should the dimensions of trust, commitment and attraction be understood in business relationships in Latin America? The study was conducted by first joining insights given by Latin American business culture literature with overall theories on the three dimensions. Through pattern matching, these insights were compared to empirical evidence collected from business professionals of the Latin American market and from the experiences of Finnish software businesses that had recently expanded into the market. What was found was that previous literature on Latin American business culture had already named many implications for the relationship marketing dimensions that were relevant also for small Finnish software firms on the market. However, key findings also presented important new drivers for the three constructs. Local presence in the area where the Latin American partner is located was found to drive or enhance trust, commitment and attraction. High-frequency follow up procedures were in turn found to drive commitment and attraction. Both local presence and follow up were defined according to the respective evidence in the study. Also, in the context of Finnish software firms in relationships with Latin American partners, the national origins or the foreignness of the Finnish party was seen to enhance trust and attraction in the relationship